Diacylglycerol kinase ζ limits IL-2-dependent control of PD-1 expression in tumor-infiltrating T lymphocytes. Issue 2 (27th November 2020) - Arranz-Nicolás, Javier; Martin-Salgado, Miguel; Rodríguez-Rodríguez, Cristina; Liébana, Rosa; Moreno-Ortiz, Maria C; Leitner, Judith; Steinberger, Peter; Ávila-Flores, Antonia; Merida, Isabel
Abstract : Background: The inhibitory functions triggered by the programmed cell death-1 (PD-1) receptor following binding to its ligand (PD-L1) protect healthy organs from cytotoxic T cells, and neutralize antitumor T cell attack. Antibody-based therapies to block PD-1/PD-L1 interaction have yielded notable results, but most patients eventually develop resistance. This failure is attributed to CD8 + T cells achieving hyporesponsive states from which recovery is hardly feasible. Dysfunctional T cell phenotypes are favored by a sustained imbalance in the diacylglycerol (DAG)- and Ca 2+ -regulated transcriptional programs. In mice, DAG kinase ζ (DGKζ) facilitates DAG consumption, limiting T cell activation and cytotoxic T cell responses. DGKζ deficiency facilitates tumor rejection in mice without apparent adverse autoimmune effects. Despite its therapeutic potential, little is known about DGKζ function in human T cells, and no known inhibitors target this isoform. Methods: We used a human triple parameter reporter cell line to examine the consequences of DGKζ depletion on the transcriptional restriction imposed by PD-1 ligation. We studied the effect of DGKζ deficiency on PD-1 expression dynamics, as well as the impact of DGKζ absence on the in vivo growth of MC38 adenocarcinoma cells. Results: We demonstrate that DGKζ depletion enhances DAG-regulated transcriptional programs, promoting interleukin-2 production and partially counteracting PD-1 inhibitory functions. DGKζ loss results in limited PD-1 expression and enhanced expansion of cytotoxic CD8 + T cell populations. This is observed even in immunosuppressive milieus, and correlates with the reduced ability of MC38 adenocarcinoma cells to form tumors in DGKζ-deficient mice. Conclusions: Our results, which define a role for DGKζ in the control of PD-1 expression, confirm DGKζ potential as a therapeutic target as well as a biomarker of CD8 + T cell dysfunctional states.